Three-body model of the final state interaction in heavy meson decay - Guimaraes, K. S. F. F.; Bediaga, I.; Delfino, A.; Frederico, T.; dos Reis, A. C.; Tomio, L. [UNESP] (Elsevier B.V., 2010)
We develop a relativistic three-body model for the final state interaction in D(+) -> K(-) pi(+) pi(+) decay based on the ladder approximation of the Bethe-Salpeter equation. The decay amplitude has the standard two-meson resonant transition matrix modulated by a spectator amplitude that carries a fully interacting three-body contribution and a smooth background term from the partonic amplitude. Our calculations are compared with D decay data.